The use of medical and drug information software programs for personal digital assistants among pharmacy students in a Malaysian pharmacy school - Elsayed, Tarek Mohamed Ali; Jamshed, Shazia Qasim; Elkalmi, Ramadan Mohamed Mahmod (Elsevier Ltd., 2015)
Background The use of medical and drug information software programs for Personal Digital Assistants (PDAs) is increasing. The technological advances in recent years may have prompted this increase. Many studies have been conducted in developed countries about the use of PDAs among health care professionals and medical and pharmacy students, but similar studies in developing countries are lacking.